Pengaruh Ukuran Perusahaan, Financial Leverage, Rerurn on Assetb(ROA), Kualitas Auditor dan Net Profit Margin (NPM) Terhadap Income Smoothing Pada Perusahaan Pertambangan Di Indonesia - kismanah, imas (Universitas Muhammadiyah Tangerang, 2018)
The aim of this study to examine the influence of firm size, financial leverage, return on asset, auditors quality and net profit margin toward income smoothing practice on mining firms are listed at Indonesia Stock Exchange. Eckel indexr (1981) was used to determine firms who did income smoothing and didn’t do income smoothing.The sample consist of mining firms that listed on period 2011-2016, which have selected as much 5 firms by purposive sampling. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. Method of data analysis used logistic regression analysis of panel data.The result of this study showed that return on asset has a negative influence to income smoothing, net profit margin has a positive influence to income smoothing. While the firm size, financial leverage and auditors quality variables did not have influence to income smoothing.